Government information resources threat: terms and determinations - Юдін, Олександр Костянтинович; Бучик, Сергій Степанович (Ukrainian Information Security Research Journal, 2014)
The analysis of the existent normatively-legal and Legislativeproviding, domestic and international standards ofindustry is conducted “Information security”. Directionswhich regulate the question of concept threat are consideredin detail, threat to informative safety, threat of information.An analytically-legal analysis on the basis ofwhich more complete concept over of threats is broughtto the state informative resources and attack on stateinformative resources is conducted. Defects are certainand absence is set in general lines approach (methodologiesof construction) of the systems to forming of modelof violator and model of threats to the state informativeresources on the base of domestic and international requirementsand standards.